25. COMPLETE PENOSCROTAL TRANSPOSITION AND BILATERAL RENAL CYSTIC DYSPLASIA. (February 2015) - Kalinowski, Lauren; Matsika, Admire; Manawwar, Sheyna; Godbolt, David
Abstract : Introduction: Complete penoscrotal transposition is a rare male genital malformation where the scrotum is located entirely cephalad to the penis. This malformation is most commonly associated with congenital abnormalities involving the genitourinary system but anomalies of the gastrointestinal, cardiovascular and the central nervous systems have also been described. Case report: We present a case of a twenty-four week old foetus with oligohydramnios, bilateral hydronephrosis, enlarged kidneys, thickened nuchal fold and abnormal limbs on antenatal ultrasound. The pregnancy proceeded to termination based on these features being incompatible with life. At autopsy, the foetus was found to have a complete penoscrotal transposition with hypospadias and urethral meatus stenosis. Both kidneys were markedly enlarged and cystic on macroscopic appearance. Microscopic examination confirmed bilateral renal cystic dysplasia with hydronephrosis. No other congenital abnormalities were identified. Discussion: There are only a small number of cases of complete penoscrotal transposition reported in the literature. An association between genital malformations, including penoscrotal transposition, and distal deletions of the long arm of chromosome 13 have been reported, with this region encoding the EFNB2 gene. A brief review of the literature and genetic associations of penoscrotal transposition ensues.